Are Learning Media Effective in English Online Learning?: The Students' and Teachers' Perceptions - Pretty Elisa Ayu Ningsih; Mike Nurmalia Sari (Tarbawi : Jurnal Ilmu Pendidikan, 2021)
This study aims to evaluate the use of learning media in English online learning activities. The evaluation is viewed from the teachers' and the students' perceptions. This research is a qualitative descriptive study with a phenomenological approach. The population in this study were all students in the seventh grade at one of the State Islamic Junior High School (MTsN) in Kerinci, Indonesia, and all of their English teachers. The sample of teachers was selected by random sampling, while the sample of students was taken by stratified random sampling. Five students were selected from each class. The instruments used in this study were questionnaires and interviews. In analyzing the interview data, the researcher reduced the data, then presented the data and then concluded, while the analysis of the questionnaire data used descriptive statistics. The study concluded that English online learning was conducted quite effectively. According to the teachers' and students' perceptions, WhatsApp Group is the most effective learning media for them. The obstacles faced by students and teachers are unstable internet networks and frequent power outages.